Efectividad del programa “Fortaleciendo el cuidado preventivo de enfermería” en el nivel de conocimientos, grado de cumplimiento de la valoración y medidas de control del riesgo de caídas en pacientes de los servicios de medicina del Hospital - Zapata Silva, Irene Mercedes (2019)
Objective: To determine the effectiveness of the program “Strengthening nursing preventive care” in the level ofknowledge of nurses, degree of compliance assessment and risk control measures for falls in patient’s medicalservices. Base Hospital Almenara Healthcare Network. Materials and Methods: quantitative, explanatory, quasiexperimental design study group and control grou The sample consisted of 80 nurses, 40 for each group, selected bypurposive sampling. During the intervention, nurses were trained, we applied the scale of John Downton, and a guideof recommendations to prevent falls. The instruments were: a questionnaire and two checklists whose reliability wasestablished using Cronbach’s alpha coefficient and Cohen’s Kappa. Results: The level of knowledge of nurses in thestudy group increased from 27.5% to 95%, while the degree of compliance with the risk assessment and risk controlmeasures fall, reached 55% in the same grou Conclusions: We found statistically significant differences accordingto Student’s t-test before and after the intervention in the three study variables between the study group and controlgroup (p <0.01 and p <0.05), confirming the hypothesis